Stable hydrogen and oxygen isotope studies of rainfall and streamwaters for two contrasting holm oak areas of Catalonia, northeastern Spain - Neal, C; Neal, M; Warrington, Anita; Avila, a (Journal of Hydrology, 1992)
Results are presented of a study of stable hydrogen and oxygen isotopes in rainfall and streamwaters for the Montseny and Prades areas in northeastern Spain: results cover the full year of 1991. The isotopic pattern for rainfall is similar for both areas: there is a wide range in isotopic contents and the results show a strong, near-linear trend, 62H = 7.9 x 6~80 + 9.8 (N = 59; r 2 = 0.952), the 'local meteoric line'. There is slight curvature to the data which may be related to the sources of water vapour forming the rainfall. Within the streams, the isotopic variability is much less than that of the rainfall although the data lie on, or very near to, the meteoric line. Data for detailed collections during storm events show more scatter than those collected regularly on a fortnightly basis. The event data show a linear feature that conforms to the local meteoric line. These results indicate that: (1) the main supply of water to the stream stormflow comes from water stored in the catchment prior to the event; (2) waters of more than one isotopic composition reside within the catchment and are transferable to the stream during storm events; (3) the main process of water transfer from the catchment back to the atmosphere comes from transpiration by the trees and (possibly) complete evaporation from the near-surface soil horizons and the tree canopy; (4) the isotopic technique cannot be used for quantitative hydrograph separation in this instance at least two water types can be present within the catchment at any given time.
Keywords: isotope composition (voyant); RAINFALL; stream water

Precipitation, throughfall, soil solution and streamwater chemistry in a holm-oak (Quercus ilex) forest - Rodà, Ferran; Avila, Anna; Bonilla, David; Rodà, Ferran (Journal of Hydrology, 1990)
Bulk precipitation, throughfall, soil solution at 20 and 40 cm depths, and stream water were monitored for 2–4 years in a holm-oak forest on schists in the Montseny Mountains (NE Spain). Bulk precipitation was mildly acidic, with Ca2+ and SO2−4 as dominant ions. Canopy interactions produced a throughfall less acidic than bulk precipitation and enriched in all other ions. Large amounts of K+ were leached from the canopy. Magnesium in net throughfall behaved similarly to K+, and it is concluded that leaching makes a major contribution to Mg2+ enrichment beneath the canopy. Judging from the moderate increase of Na+ and Ca2+ in throughfall, dry deposition rates for both marine and continental aerosols were low in the studied stand, probably because of its sheltered topographic position within a well-vegetated massif, coupled with moderate tree height and low canopy roughness. Soil solution in the mineral soil was less acidic than throughfall. In common with most temperate forests, SO2−4 was the dominant mobile anion in the soil water, being largely accompanied by Ca2+. Potassium and NO−3 were depleted within the soil water with respect to throughfall, probably owing to biological uptake and cation exchange, and incorporation of K+ into clay lattices. Subsurface flow dominated the hydrology of the small forested catchment studied. Stream water was basic and rich in bicarbonate. Its chemistry revealed fast rates of weathering of sodium- and magnesium-bearing silicates (mainly albite and chlorite, respectively). Soil respiration and silicate hydrolysis resulted in HCO−3 being the dominant mobile anion in stream water. Calcium to chloride ratios were similar in bulk precipitation and in stream water, indicating that Ca2+ release from weathering has been counteracted by plant uptake. Nutrient uptake by this aggrading forest strongly influences the solution dynamics of K+, NO3 and Ca2+. It is concluded that: (1) this forest does not currently receive acidic atmospheric deposition; (2) the neutralization capacity of the soil-bedrock system is quite high; (3) biotic regulation and silicate weathering are the major processes shaping the solution biogeochemistry in this Mediterranean forest ecosystem.
Keywords: Canopy; chemistry (voyant); Holm oak; Montseny mountains; Precipitation; soil solution; stream water; throughfall